Prevalence of asymptomatic malaria and associated factors among pregnant women in Ethiopia: systematic review and meta-analysis - Duguma, Tadesse; Tekalign, Eyob; Kebede, Samuel Sahile; Bambo, Getachew Mesfin (Frontiers in Reproductive Health, 2023)
The proactive identification of asymptomatic patients and the mitigation of associated problems are essential to the elimination of malaria. For asymptomatic malaria and related variables among pregnant women in Ethiopia, there are no national pooled estimates. As a result, the goal of this study is to compile thorough and compelling data from several Ethiopian investigations. Google Scholar, PubMed, Scopes, the Web of Science, the Cochrane Library, and African Journals Online were a few of the electronic resources that were accessed. The investigation included all observational studies. STATA version 15 was used to extract the data from the Microsoft Excel file and conduct the analysis. The estimated pooled prevalence of asymptomatic malaria among pregnant women was calculated using a random-effects model. An inverse variance index (I2) analysis was utilized to find heterogeneity. To assess the publication bias, funnel plots, and Egger's statistical tests were used. The study determined that the combined prevalence of asymptomatic malaria among pregnant women was 7.20 (95% confidence interval = 4.22, 10.18) and 4.69 (95% confidence interval = 2.77, 6.62) by microscopy and rapid diagnostic test, respectively. The presence of stagnant water near their home (odds ratio = 4.31; 95% confidence interval = 1.66, 11.20); not using insecticide-treated nets (odds ratio = 6.93; 95% confidence interval = 3.27, 14.71); the lack of indoor residual spray service (odds ratio = 2.68; 95% confidence interval = 1.63, 4.40); and the presence of pregnant women in their neighborhood (odds ratio = 3.14; 95% confidence interval = 1.4). This study showed that pregnant women have a high pooled prevalence of asymptomatic malaria. Women living in rural areas near stagnant water and those who never used insecticide-treated nets had a two-, four-, or six-fold higher prevalence of asymptomatic malaria, respectively. The use of advanced diagnostic techniques could produce a higher magnitude of the disease. For effective intervention toward elimination, active case detection at the community level is also advised. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023411385; identifier, CRD42023411385.